Pendampingan Pengembangan Potensi Bidang Bahasa, Seni Sastra, dan Seni Pertunjukan Jawa di Desa Beji Kecamatan Ngawen Kabupaten Gunungkidul Menuju Desa Berbudaya Jawa - Djarot Heru Santosa (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
A village having potential of cultures, especially language, literature, and performing arts is getting more difcult to be found in this millenium era. When the condition is owned by a certain village, it is natural to be accompanied in growing and strengthening the self-awareness of the villagers by maintaining, preserving, and developing those potentials. One of the villages that has potential of Javanese cultures, especially language, literature, and performing arts is Beji Village. Te location of the village is in Ngawen District, Gunungkidul, DIY.Observation and inventory of problems, mapping the problems, taking action in the form ofgiving motivation, counseling, education, and opening the discussion and consultation as widely as possible are the methods of the accompaniment. By implementing those methods, optimal results namely changes in community behavior in terms of awareness, understanding improvement, and capability to manage the potential feld of language, literature, and performing arts that they already have will be achieved.The result of community service in Beji Village, especially in the feld of language shows someerrors and inaccurate uses of the Javanese variety language in daily routine. In addition, there was also some correction and education in writing Java letters in the nameplate in the sub villages. In the literature feld, accompanied by the local society, we succeeded in documenting the writing of folklore based on some heritage sites in the village. In performing arts, not only succeeding in education and counseling, we also established the institutional art groups in the village of Beji.